Interplanting potato with grapes improved yield and soil nutrients by optimizing the interactions of soil microorganisms and metabolites - Li, Chengchen; Xie, Yuming; Liao, Yongshan; Liu, Jitao; Li, Bin; Lu, Yusheng; Yang, Kun; Shan, Jianwei; Wang, Li; An, Kang; Zhou, Xiaoqi; Cheng, Xu; et al. (Frontiers in Plant Science, 2024)
Interplanting crops is the best method to grow crop synergistically for better utilization of land and agro-resources. Grape (Vitis vinifera) and potato (Solanum tuberosum L.) serve as highly efficient agricultural planting systems in China, however, how soil physicochemical properties, soil microbial communities and metabolites affects the output of grape-potato interplanting remained unknown. In this study, we employed three planting patterns (CK: grape monocropping; YY: grape interplanted with potato (variety ‘Favorita’); LS: grape interplanted with potato (variety ‘Longshu7’) at two experimental sites i.e., the Huizhou (2022) site and the Qingyuan (2023). The grape variety for all planting patterns was ‘Sunshine Rose’. Soil samples (top 0-20 cm) at both sites were collected to observe the diversity of bacterial communities and soil metabolites. Our findings revealed that, compared with monocropping, the interplanted systems resulted in higher concentrations of total nitrogen, available phosphorus and available potassium and enhanced the activities of acid phosphatase, urease and protease. The potato root exudates also altered the relative abundance of Bacillus, Kaistobacter and Streptomyces in the rhizosphere. Among the soil metabolites, lipids and organic acids showed the most significant changes. Notably, 13-L-hydroperoxylinoleic acid is the key differentially abundant metabolite involved in the regulation of linoleic acid metabolism pathways. The association analyses of the metabolome, microbiome and soil physicochemical properties revealed that the interactions of microbes and metabolites resulted in differences in the soil nutrient content, whereas the interactions of 13-L-hydroperoxylinoleic acid and Firmicutes improved the soil nutrient levels and bacterial composition in the interplanting systems. In sum, our findings demonstrated that intercropping grapes with potato ‘Favorita’ was better with respect to improve soil nutrients, soil enzyme activity, the diversity of soil bacteria and soil metabolites without causing adverse impacts on grape yield. Overall, this study explained the physiological mechanisms by which soil microorganisms and metabolites promote potato growth in grape interplanting and provided new perspectives for the utilization of soil resources in vineyards.